Development of Lumi Education Learning Media Based on H5P for Atmospheric Dynamics Subject at Senior High School 1 Gorontalo - S. Matana, Mohamat Doni; Maryati, Sri; Koem, Syahrizal (Universitas Lambung Mangkurat, 2024)
The results of observations made at senior high school 1 Gorontalo show that some teachers have not been able to make interactive media so that the teaching and learning process still uses printed books. This study aims to development of Lumi education learning media based H5P on atmospheric dynamics material. The method used in this study is a type of development research with the ADDIE model as an approach in preparing the learning media. This research is conducted using the ADDIE development model, which consists of five stages that is information gathering stage (analysis), planning stage (design), development stage, validation and testing stage, evaluation. The results of this study can be concluded that the development of Lumi education learning media based H5P has passed a validity test by material experts who got a score percentage of 88.3%, the next validator is a product expert validator who got a score percentage of 85.4% and the last by a learning expert validator who gets a percentage of 90% so that it can be used in the learning process in the classroom related to the basic atmospheric dynamics.